Kontekstualisasi Nilai Budaya Hatulwikna (Gotong Royong) Dalam Pembelajaran Tematik Pada Kurikulum Merdeka: Studi Kasus Di Sekolah Dasar Di Sumba Barat - Daud Moma Bili; Erni Murniarti; Bernadetha Nadeak (LPPM Institut Pendidikan Nusantara Global, 2026)
Education in Indonesia is currently directed toward improving contextual and character-based learning through the implementation of the Merdeka Curriculum. One approach that can be applied is the integration of local cultural values in the learning process. This study aims to analyze the implementation of the Hatulwikna cultural value (mutual cooperation) in thematic learning at an elementary school in West Sumba. This research used a qualitative case study design. The subjects of this study were the principal, teachers, and students. Data collection techniques used interviews, observation, and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results of this study show that the Hatulwikna value has been implemented in the learning process through three stages, namely planning, implementation, and evaluation. In the planning stage, the value has been integrated into learning objectives, although not explicitly written in teaching modules. In the implementation stage, the value is reflected through group work activities and collaborative interactions among students. In the evaluation stage, assessment has included attitudes and student participation, although it has not yet used specific instruments based on local cultural values. Based on these results, it can be concluded that the integration of Hatulwikna values in thematic learning can support the development of students’ character and create meaningful learning, although it still requires improvement in systematic planning and evaluation.